Nazi mega weapons. [Season 1] [videorecording (DVD)] : German engineering in WWII - Hale, Chris (Christopher); McLaughlin, Luke; Baker, Steve (Director); Johnson, Corey (PBS, 2013)
In the quest for world domination, the Nazis built some of the biggest and deadliest pieces of military hardware and malevolent technology in history. Nazi Mega Weapons follows a group of experts on a dark journey through Europe's mountains, forests and beaches to uncover engineering secrets that have lain hidden for decades and the stories of the men that designed them.